Pengaruh Supervisi Akademik Kepala Sekolah, Motivasi Kerja dan Disiplin Kerja terhadap Kinerja Guru SMP Negeri di Sub Rayon 3 Temanggung - Minawati, Madinatun; Egar, Ngasbun; Abdullah, Ghufron (Jurnal Inovasi Pembelajaran di Sekolah, 2023)
Teacher performance can be interpreted as the teacher's ability to carry out his duties as a teacher who has the expertise to educate students and develop students to achieve the goals of an educational institution. This research aims to (1) determine the influence of the principal's academic supervision on teacher performance, (2) determine the effect of work motivation on teacher performance, (3) determine the influence of work discipline on teachers, and (4) determine the influence of the principal’s academic supervision, work motivation, and work discipline on teacher performance. This research used a quantitative, correlational approach. The population in this study were all State Junior High School teachers in Sub Rayon 3 Temanggung, totaling 322 teachers. Meanwhile, the research sample consisted of 178 teachers spread across 11 schools. Then, the data collection method used a questionnaire. Data analysis techniques used descriptive statistical analysis, regression analysis, analysis tests, and hypothesis testing using SPSS. The research results showed (1) the principal's academic supervision partially had a significant effect on teacher performance with the results of tcount > ttable (8.349 > 1.65356) and sig. 0.000 < 0.05, and the magnitude of the effect is 28.4%; (2) work motivation partially has a significant effect on teacher performance with the results of tcount > ttable (11.612 > 1.65356) and sig. 0.000 < 0.05, and the magnitude of the effect is 43.4%; (3) work discipline partially has a significant effect on teacher performance with the results of tcount > ttable (7.739 > 1.65356) and sig. 0.000 < 0.05, and the magnitude of the effect is 25.4%; and (4) the principal's academic supervision, work motivation, and work discipline simultaneously (together) have a significant effect on teachers performance with the result of a Fcount > Ftable value of 60.618 > 2.26 and a sig value of 0.000 < 0.05 and the magnitude of the simultaneous influence amounting to 51.5%.